Tutor Support as a Tool of Social-Cultural Adaptation ofInternational Students in Russian Universities - O. A. Beregovaya; S. S. Lopatina; N. V. Oturgasheva (Высшее образование в России)
In the conditions of increasing internationalization of higher education, attracting students from abroad is considered as one of the means of strengthening the country’s position in the world educational space. At the same time, the implementation of this indicator is complicated by the need to systematically, comprehensively change the educational and educational process and create favorable conditions for students from among foreign citizens. The purpose of this article is to consider tutor support as a tool of sociocultural adaptation of international students and its application in Russian universities. The authors analyze the concepts of “socio-cultural adaptation”, “tutor support” and show their relationship.The article considers such principles of modern education as openness, variability, dialog, individualization, creation of open information environment, and shows compliance with these principles of tutor support practice. The program of training of student tutors is presented and the content and forms of implementation of educational modules of this program are revealed.As a result of the analysis of the experience of the School of tutors and volunteers in Siberian Institute of management, the branch of RANEPA it is concluded about the prospects and opportunities of using student tutoring as a tool for adapting international students to study in Russian universities and an effective way of their involvement in joint sociocultural activities, allowing to reveal and develop their existing personal and educational potential. The experience of training students-tutors is aimed at creating favorable conditions for socio-cultural adaptation of international students in Russia.